2021
DOI: 10.1051/0004-6361/202140665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optically thin cooling curves on condensation formation: Case study using thermal instability

Abstract: Context. Non-gravitationally induced condensations are observed in many astrophysical environments. In solar physics, common phenomena are coronal rain and prominences. These structures are formed due to energy loss by optically thin radiative emission. Instead of solving the full radiative transfer equations, precomputed cooling curves are typically used in numerical simulations. In the literature, a wide variety of cooling curves exist, and they are quite often used as unquestionable ingredients. Aims. We he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 95 publications
3
35
0
Order By: Relevance
“…The condensations that are entrapped within the coalescing plasmoids thereby also show rapid variations of the radiative losses across their edges, much like the prominence corona transition region (PCTR), also at play for individual coronal rain blobs. Note that the precise variation of temperature, density and radiative losses is here not incorporating effects of anisotropic thermal conduction, and therefore we have extremely sharp transitions, as explained also in (Hermans & Keppens 2021).…”
Section: Global Evolutionmentioning
confidence: 95%
“…The condensations that are entrapped within the coalescing plasmoids thereby also show rapid variations of the radiative losses across their edges, much like the prominence corona transition region (PCTR), also at play for individual coronal rain blobs. Note that the precise variation of temperature, density and radiative losses is here not incorporating effects of anisotropic thermal conduction, and therefore we have extremely sharp transitions, as explained also in (Hermans & Keppens 2021).…”
Section: Global Evolutionmentioning
confidence: 95%
“…The evolution of the condensations depends on one hand on the thermal instability regime, and in particular on the inflow velocity u = n R /k, which can lead to fragmentation effects due to strong oscillations in size, temperature and density. On the other hand, Hermans and Keppens (2021) have shown that the cooling curve chosen for the treatment of the radiative losses, and in particular the treatment at low temperatures (<20 000 K), greatly varies the growth rate of the instability and the morphology of the condensations. This theory has been applied to the formation of coronal rain and prominences in the solar context.…”
Section: Local Scales: Thermal Instabilitymentioning
confidence: 99%
“…Testing the viability of this model will require solving the equations of radiation MHD (RMHD). Advances in understanding of the dynamics of TI in MHD have been led by the solar physics community in recent years (see reviews by Antolin & Froment 2022;Soler & Ballester 2022), especially in the context of solar prominence formation and the coronal rain phenomenon (e.g., Claes & Keppens 2019;Claes et al 2020;Hermans & Keppens 2021). Because these studies have all assumed an optically thin formalism where attenuation is neglected, we stress that the RHD framework and analysis methods presented here are equally applicable to the equations of RMHD.…”
Section: Discussionmentioning
confidence: 99%